Perceptions of Pre-clinical Science Faculty Members Regarding Problem Based Learning at Manipal College of Medical Sciences - Basnet, Sahisnuta (Nepal Journal of Medical Sciences, 2025)
Introduction: Problem-Based Learning (PBL) is a student-centered instructional method that enhances critical thinking, teamwork, and knowledge retention. At Manipal College of Medical Sciences (MCOMS), PBL has been integrated into the pre-clinical sciences curriculum. Understanding faculty perceptions of this pedagogical method is essential for optimizing its implementation. This study aimed to assess the perceptions of pre-clinical science faculty members at MCOMS regarding the effectiveness and challenges of PBL in medical education. Methods: A descriptive cross-sectional study was conducted among 30 faculty members from seven pre-clinical departments at MCOMS. Data were collected using a structured questionnaire containing 30 perception items rated on a five-point Likert scale. Responses were analyzed using SPSS version 20, and Kruskal-Wallis tests were employed to explore associations with faculty characteristics. Results: Faculty perceptions toward PBL were generally favorable. More than 85% agreed that PBL improves knowledge retention, student engagement, communication skills, teamwork, and critical thinking. However, significant concerns were reported about inadequate faculty training, lack of assessment clarity, and unsuitable classroom infrastructure. A statistically significant difference in perception was observed among the oldest age group (p=0.020), but not with other demographic variables. Conclusion: Faculty members value PBL for its educational benefits but identified gaps in training and institutional support. To maximize the impact of PBL, structured faculty development programs and logistical improvements are recommended.